2017
DOI: 10.1177/0194599817711886
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics in Thyroid Surgery: The Patient Perspective

Abstract: Objectives To define characteristics that influence patient perceptions of thyroidectomy scar cosmesis. Study Design Prospective cohort study. Setting Tertiary endocrine surgery practice in an academic medical center. Subjects and Methods Institutional review board-approved trial in which 136 subjects were recruited from a population of patients being seen for either thyroid or sinus surgery and evaluated standardized photographs, superimposed with computer-generated thyroidectomy scars of varying lengths (2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
0
21
2
Order By: Relevance
“…Another aspect of importance after thyroid surgery, especially from the patient perspective, is the cosmetic appearance of the cervical scar. Using the validated POSAS tool, no difference in cervical scar cosmesis was found in the present trial, either from the patient or observer perspective.…”
Section: Discussioncontrasting
confidence: 53%
“…Another aspect of importance after thyroid surgery, especially from the patient perspective, is the cosmetic appearance of the cervical scar. Using the validated POSAS tool, no difference in cervical scar cosmesis was found in the present trial, either from the patient or observer perspective.…”
Section: Discussioncontrasting
confidence: 53%
“… 5 , 6 To combat scars, surgical procedures are designed to limited the visible impact of scars by a variety of techniques, including positioning scars in favorable, less visible locations, orienting scars parallel to Langer’s lines, and reducing scar length (eg, minimally invasive or endoscopic techniques). 7 , 8 Patients may decline surgery altogether or be driven toward noninvasive treatments due to scar concerns. More than 180,000 scar revisions are performed in the United States on an annual basis, 9 leading to patient discomfort, lost productivity, and cost.…”
mentioning
confidence: 99%
“…Another objective of this study was to investigate whether casual observer race and gender identity influenced observer visual attention. Chaung et al 9 reported that nonwhite patients had measurably different perceptions of neck scars than white patients. In particular, nonwhite patients appeared to rate computer-generated neck scars harsher than their white counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…8 Patients and observers across the spectra of age, sex, and race universally prefer shorter and thinner scars following neck surgery. 9 Interestingly, non-Caucasian patients tend to rate neck scars worse and penalize longer and thicker scars more when compared to Caucasians. 9 This may be related to predispositions of certain skin types to hypertrophic or keloid scarring as well as cultural differences in the perception of scarring given regional variation in the popularity of scarless surgical approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation